2014
DOI: 10.1016/j.meegid.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Full genomic characterization of a novel genotype combination, G4P[14], of a human rotavirus strain from Barbados

Abstract: Since 2004, the Pan American Health Organization (PAHO) has carried out rotavirus surveillance in Latin America and the Caribbean. Here we report the characterization of human rotavirus with the novel G-P combination of G4P[14], detected through PAHO surveillance in Barbados. Full genome sequencing of strain RVA/Human-wt/BRB/CDC1133/2012/G4P[14] revealed that its genotype is G4-P[14]-I1-R1-C1-M1-A8-N1-T1-E1-H1. The possession of a Genogroup 1 (Wa-like) backbone distinguishes this strain from other P[14] rotavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 51 publications
(55 reference statements)
1
30
3
Order By: Relevance
“…1a) indicated that strain RVA/Human-wt/DOM/2013840364/2013/G4P[6–8_R] grouped into a sublineage within lineage VII [19], which comprised porcine strains HLJkd from China, Ro1 from India, ICB2185 from Brazil and P30 from Argentina. Strains in this lineage shared moderate nucleotide and amino acid identities in the range of 85.8–91.5% and 91.7–93.9 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a) indicated that strain RVA/Human-wt/DOM/2013840364/2013/G4P[6–8_R] grouped into a sublineage within lineage VII [19], which comprised porcine strains HLJkd from China, Ro1 from India, ICB2185 from Brazil and P30 from Argentina. Strains in this lineage shared moderate nucleotide and amino acid identities in the range of 85.8–91.5% and 91.7–93.9 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The G/P combination of G4P[6–8_R] on entirely a genogroup 1 genetic backbone showed that this strain was formed though a single genetic reassortment event in which a G4P[8]-like strain with a typical genogroup 1 background acquired the neutralization antigen (VP7) from a porcine-like G4 strain that most likely circulated locally. This evidence is supported by the fact that the VP7 gene of strain RVA/Human-wt/DOM/2013840364/2013/G4P[6–8_R] clustered with porcine and porcine-like human rotaviruses in lineage VII [19]. Also, with the exception of the recombinant VP4, NSP1 and NSP3 gene segments, the remaining seven gene segments (VP1-VP3, VP6, NSP2, NSP4 and NSP5) clustered with rotaviruses of human origins belonging to cognate gene sequences of genogroup 1 genotypes.…”
Section: Discussionmentioning
confidence: 97%
“…A variety of G4P[6] strains were found to be either zoonotic porcine strains or human-porcine reassortants. G4P[6] strains were detected in Hungary sporadically over a 15-year period, with each strain representing an independent interspecies [110,111]. It is postulated that the events that could lead to multi-host origin rotavirus genotype constellations may be sequential acquisition of genes from a common gene pool of any geographic area in a single host or alternating host species.…”
Section: Evidence and Mechanisms Of Rotavirus Zoonosismentioning
confidence: 99%
“…An Australian G3P[14] strain was detected that had a mixture of bat, feline/canine and bovine Rotavirus genes. A G4P [14] strain from Barbados may be a reassortant of human, porcine and bovine Rotaviruses (Donato et al, 2014;Tam et al, 2014 …”
Section: Rotaviruses In Humansmentioning
confidence: 99%
“…RVA strains are classified into P types (for protease-sensitive) and G types (for glycoprotein) respectively (Estes and Kapikian, 2007). At least 27 G types and 35 P types have been described so far (Matthijnssens et al, 2011a;Banyai et al, 2012;Tam et al, 2014). The Rotavirus Classification Working Group has now established a naming manual including (a) the segment's serotype group, (b) the type of the host (c) the country of detection of the strain, (d) the name that was given to the segment, (e) the year of detection and (f) its genotype combination of the GxP[x] format i.e.…”
mentioning
confidence: 99%